Improving Students' Listening Skills Using Watching Movie - Ghisela Stefany Putri; Afldy Nurseri Sihotang; Sri Ninta Tarigan; Karisma Erikson Tarigan (INTERACTION: Jurnal Pendidikan Bahasa, 2023)
This essay explores a strategy for teaching pupils to listen better. It necessitates that students practice listening both within and outside of the classroom. Several activities can be carried out, and various media can be employed to provide children with listening activities to hone their listening abilities. Watching movies is one of the students' favorite pastimes. Students are introduced to the language's context and vocabulary through the film. The task of writing a film report was given to the class after the movie. Giving pupils the task of watching movies and writing reports, since many individuals enjoy doing so on what they viewed, greater enjoyment is anticipated. But before they write a report, they must comprehend the movie itself. Before creating and presenting a film report in class, they may need to watch the movie twice or even more to comprehend it fully. To complete this activity, the students must hear the characters' words, expressions, and sentences. This activity has a variety of advantages. Students can learn pronunciation and practical phrases from native speakers by viewing movies. Along with these tasks, students had to compose a summary of the movie, decipher the meaning of useful words, comprehend the story's moral, and give their reports.